Educational Socialization as Parental Empowerment in Shaping Early Childhood Character in the Society 5.0 Era: Sosialisasi Edukatif Sebagai Pemberdayaan Orang Tua dalam Membentuk Karakter Anak Usia Dini di Era Society 5.0 - Sulaiman, Muhammad; Nurfaiza, Nurfaiza; Wildan, Labibul; Fatholla, Fatholla (Al Busyro : Jurnal Pengabdian Kepada Masyarakat, 2025)
The Community Service Program (PKM) aims to empower parents in shaping early childhood character in the Society 5.0 era, especially in Nyiur Cangka Hamlet, Kesambirampak Village, Kapongan District, Situbondo Regency. The main problems found are traditional parenting, low digital literacy, and lack of parental awareness of the importance of character education in the midst of rapid technological currents. The activity was carried out using the Participatory Action Research (PAR) method through the stages of problem identification, planning, educational socialization, and participatory evaluation. The results of the activity showed an increase in parents' understanding of the importance of authoritative parenting that balances affection, discipline, and supervision. Parents are beginning to realize the impact of excessive use of gadgets, the importance of habituating positive behavior, and strengthening moral values in children's lives. In addition, interactive discussion forums provide a space for parents to share experiences and gain practical skills that can be applied immediately. In conclusion, parental empowerment has proven to be effective in increasing the capacity of families to form children who are resilient, disciplined, and adaptive to changing times. The recommendation of this program is the need for the sustainability of similar activities with the support of schools, community leaders, and the integration of digital literacy so that it can become a contextual character education model in the Society 5.0 era.